Fiscal disobedience : an anthropology of economic regulation in Central Africa - Roitman, Janet L. (Janet Lee) (In-formation series., 2005)
"Fiscal Disobedience represents a novel approach to the question of citizenship amid the changing global economy and the fiscal crisis of the nation-state. Focusing on economic practices in the Chad Basin of Africa, Janet Roitman combines thorough ethnographic fieldwork with sophisticated analysis of key ideas of political economy to examine the contentious nature of fiscal relationships between the state and its citizens. She argues that citizenship is being redefined through a renegotiation of the rights and obligations inherent in such economic relationships. The book centers on a civil disobedience movement that arose in Cameroon beginning in 1990 ostensibly to counter state fiscal authority--a movement dubbed Operation Villes Mortes by the opposition and incivisme fiscal by the government (which for its part was eager to suggest that participants were less than legitimate citizens, failing in their civic duties). Contrary to standard approaches, Roitman examines this conflict as a 'productive moment' that, rather than involving the outright rejection of regulatory authority, questioned the intelligibility of its exercise. Although both militarized commercial networks (associated with such activities trading in contraband goods including drugs, ivory, and guns) and highly organized gang-based banditry do challenge state authority, they do not necessarily undermine state power."--Publisher's description